Safety and Pharmacokinetics of XOMA 3AB, a Novel Mixture of Three Monoclonal Antibodies against Botulinum Toxin A - Nayak, S. U. (American Society for Microbiology, 2014)
Botulinum neurotoxin A is a category A bioterrorism agent. Current antitoxin therapies are scarce and produce adverse reactions. XOMA 3AB consists of 3 IgG1 monoclonal antibodies (MAbs), each with a distinct human or humanized variable region, which bind to distinct epitopes on botulinum neurotoxin serotype A. This first-in-human study evaluated the safety and pharmacokinetics (PK) of escalating doses of XOMA 3AB administered intravenously (i.v.) to healthy adults. In this double-blind placebo-controlled dose escalation study, 3 cohorts of 8 healthy subjects received a single intravenous dose of XOMA 3AB or placebo at a 3:1 ratio. Follow-up examinations included physical examinations, hematology and chemistry blood tests, electrocardiograms, and pharmacokinetics. Pharmacokinetic parameters were estimated using noncompartmental methods. There were no infusion discontinuations or hypersensitivity reactions. Two or more subjects experienced headache, hyperglycemia, or anemia; none was dose related. All adverse events (AEs) were mild to moderate except for an episode of exercise-induced elevation of a subject's creatine phosphokinase (CPK) level, unrelated to XOMA 3AB. Concentration-time plots demonstrated a peak in MAb concentrations 1 to 2 h after completion of the infusion, after which the levels declined in a biexponential decay pattern for all analytes. For each MAb, the maximum concentration of drug in serum (C(max)) and the area under the concentration-time curve from 0 to infinity (AUC(inf)) increased as the dose increased. Clearance of the humanized mouse MAb was more rapid than that of the two fully human MAbs, particularly at the lowest dose. None of the MAbs was immunogenic. At the doses administered, XOMA 3AB was well tolerated. These safety findings support further investigation of XOMA 3AB as a potential agent for botulism treatment and postexposure prophylaxis. (This study has been registered at ClinicalTrials.gov under registration no. NCT01357213.)